Route Choice Behavior Analysis with Unexpected Delay Information - Yu, Yao; Zhou, Xi-Zhao (Procedia engineering, 2016)
Route choice behavior analysis has been widely adopted to promote intelligent traffic systems running efficiently. For better grasp the route choice behavior characteristic under some uncertain environments, a practical influential factor of unexpected delay is proposed and invested for urban travel in daily. The parameter of unexpected delay not only can well describe the travelers’ sensitivity of travel time and its accurate, but also greatly influence traveler's judgment for different travel modes. It is important for route choice behavior analysis under uncertain conditions. According to the above, this paper sets multi-subject probability to construct uncertainly traffic environment to analyze the attitude of route choice combine with MEU (maxmin expected utility) theory under risky scenario. The experiments indicate that 95% travelers show risky preference when they in a route choice setting. Furthermore, the sensitivity of delay time is closely relation in proportion to the entire travel time refer to diminishing marginal utility by travelers. Finally, the results also elaborate the phenomenon of the small probability overestimate contrast to the high probability underestimate of the delay probability.